Menelaâ€™ah Konsep Maqasid Al-Shariâ€˜Ah Al-Juwayni dalam Kitab Al-Burhan Fi Usul Al-Fiqh - Nasiri Nasiri (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2015)
Abstract: Abu al-Ma'ali al-Juwayni, a high-caliber jurist is well known as Imam al-Haramayn. His appearance brought forward a work on original usul al-fiqh which was different from the written style of the previous usul al-fiqh books as well as provided tremendous influence to the writing of the later books. His description about the law methodology, in his work namely al-Burhan fi Usul al-Fiqh, was a valuable original finding that differentiates him from the other authors of the usul books. One of his original ideas which was his first breakthrough in the field of usul al-fiqh was the concept of maqasid al-shari'ah, to which he divided it into two parts: "the unwritten maqasid" that was achieved through istiqra' way and â€œwritten maqasidâ€ that was achieved through coherence (qarinah) which were divided into contextual coherence (qarinah haliyyah) and verbal coherence (qarinah maqaliyyah) through the ways of exception (istithna ') and specialization (takhsis).